Evaluation of asphalt binder blended with coconut coir dust and residual coconut fibers for structural applications (2018)
This is an investigation into asphalt binder mixed with different amounts of an organic waste containing coconut coir dust and residual short coconut fibers abundant in the Caribbean and tropical countries. The concentrations used were 0.0, 1.0, 2.5 and 5.0wt%. Coconut coir is a type of organic waste produced in large quantities in Caribbean region of Colombia. It is composed of grinded mesocarp, which is the fibrous husk of the coconut fruit, and is currently used in agriculture, ornaments and crafts. This waste is a very stable and strong material suitable for use in structural applications such as the reinforcement of composite materials. In this investigation, materials characterization was conducted using Fourier transform infrared spectroscopy and scanning electron microscopy to analyze the microstructure of samples. Particle size distribution tests were also included to analyze the short coconut fibers. Penetration, softening point, penetration index, viscosity, flash point, fire point and ductility performance tests were also carried out on the asphalt mixes. Overall, these tests revealed that asphalt formulations can be used in selected construction and building material applications.